Access to α, β-unsaturated carboxylic acids through water-soluble palladium catalyzed hydroxycarbonylation of alkynes using water as the solvent. Issue 14 (30th June 2021) - Lv, Jinhe; Zong, Lingbo; Zhang, Jinrong; Song, Jiaxin; Zhao, Jinyu; Zhang, Kai; Zhou, Ziqin; Gao, Mingjie; Xie, Congxia; Jia, Xiaofei; Ren, Xinyi
Abstract : A reusable water-soluble Pd(OAc)2 /sulfoxantphos catalyst has been developed for the hydroxycarbonylation of symmetrical and unsymmetrical alkynes with CO/H2 O to afford the corresponding α, β-unsaturated carboxylic acids in good yields. Abstract : A sulfoxantphos modified palladium-catalyzed synthesis of α, β-unsaturated carboxylic acids from alkynes with CO and H2 O was described. The atom-economic hydroxycarbonylation of various symmetrical and unsymmetrical alkynes can be achieved with chemo-, stereo-, and regioselectivity, affording the corresponding carboxylic acids in good to excellent yields. Using water as the reaction solvent, the water-soluble palladium catalyst was easily separated from the product and could be reused for 5 cycles.